A case study of an ORC geothermal power demonstration system under partial load conditions in Huabei Oilfield, China. (December 2017) - Hu, Kaiyong; Zhu, Jialing; Zhang, Wei; Lu, Xinli
Abstract: Liubei reservoir of Huabei oilfield, a typical mature oil and gas field in China, now has a water cut of 98% and the traditional "oil" field has become a "water" field. To further exploit the oilfield, a 500kW organic Rankine cycle using R245fa as the working fluid was designed and set up to use the coproduced fluid. Experiments under partial load conditions indicate that it is a good choice to use a plate heat exchanger as the preheater to be responsible for part load of the evaporator. In addition, dynamic test results show that the fluctuating of the geothermal water strongly affects the stability of the system's performances, so attention should be paid on the stability of the geothermal water flow rate. Compared with the design generating capacity, the system did not get as much electricity as expected. Besides, exergy comparison analysis between design and partial load condition reveals that the intermediate heat exchanger (IHE) used to transfer heat from geothermal water to hot water becomes the main obstacle in view of exergy utilization ratio. Therefore, methods should be adopted to decrease the heat transfer temperature difference between the geothermal water and hot water, to reduce the exergy loss of the system.